Heavy Metal and Biochemical Content of Sargassum Wightii Occurring in Tuticorin Coast, Tamil Nadu, India - A. Brabakaran, N. Jothinayagi, C. Anbazhagan (Journal of Phytology, 2009)
Investigations have been made to study the heavy metal composition of Sargassum wightii occurring in Tuticorin, Tamil Nadu. Different parts of S. wightii such as stem, leaf receptacle and air-bladder were subjected to the scrutiny of heavy metals such as Cd, Cr, Cu and Fe present in those parts of brown algae under atomic absorption spectrophotometer. The highest concentration of Cd was observed in leaf and lowest in air-bladder of S. wightii. The maximum level of Cr was observed in air bladder and low in stem. The concentration of copper was higher in stem, low in leaf of S. wightii. The accumulation of iron in receptacle was higher and lower in air bladder of S. wightii. Biochemicals such as total carbohydrate, total protein and total lipid contents were also estimated. The results showed that the protein content of S. wightii was higher than lipid and carbohydrate.